Giant cell arteritis: Current treatment and management - Ponte, C; Rodrigues, A; O'Neill, L; Luqmani, R (Baishideng Publishing Group, 2015)
Glucocorticoids remain the cornerstone of medical therapy in giant cell arteritis (GCA) and should be started immediately to prevent severe consequences of the disease, such as blindness. However, glucocorticoid therapy leads to significant toxicity in over 80% of the patients. Various steroid-sparing agents have been tried, but robust scientific evidence of their efficacy and safety is still lacking. Tocilizumab, a monoclonal IL-6 receptor blocker, has shown promising results in a number of case series and is now being tested in a multi-centre randomized controlled trial. Other targeted treatments, such as the use of abatacept, are also now under investigation in GCA. The need for surgical treatment is rare and should ideally be performed in a quiescent phase of the disease. Not all patients follow the same course, but there are no valid biomarkers to assess therapy response. Monitoring of disease progress still relies on assessing clinical features and measuring inflammatory markers (C-reactive protein and erythrocyte sedimentation rate). Imaging techniques (e.g., ultrasound) are clearly important screening tools for aortic aneurysms and assessing patients with large-vessel involvement, but may also have an important role as biomarkers of disease activity over time or in response to therapy. Although GCA is the most common form of primary vasculitis, the optimal strategies for treatment and monitoring remain uncertain.